Parenting Dynamics in wrking families and their influence on adolescent behavior in Surabaya - Marcela, Jesica Gita; Ridwan, Ahmad (Universitas Ahmad Dahlan, 2025)
This study will investigate the dynamics of parenting in working families and its implications for adolescent behavior in Surabaya. In families where both parents are employed, parenting faces various challenges that affect emotional closeness and character development among adolescents. Using a qualitative phenomenological approach, data were collected through in-depth interviews and non-participant observation of adolescents aged 16–19 years. The findings reveal that limited time with parents leads to minimal emotional communication, causing teenagers to internalize personal issues or prefer to share them with peers. On the other hand, this condition also fosters independence, responsibility, and strong social awareness. These findings are analyzed using George Herbert Mead’s role theory, indicating that adolescents indirectly take on parental roles at home. The identity formation process occurs earlier, though at the expense of emotional warmth and interaction within the family.